Qualitative Analysis of Christian Religious Education Teacher Learning Strategies in Online Learning - Dian Paskarina; Ludwig Beethoven Jones Noya; Pratiwi Eunike; Bobby Kurnia Putrawan (Didache: Journal of Christian Education, 2021)
In the era of the Covid-19 pandemic, distance or online learning has become the primary method used by the government, in this case the Ministry of Education and Culture, to prevent the increasing number of Covid-19 viruses and the emergence of clusters in schools. In online learning, PAK teachers in their multifunctional role need to apply contextual learning strategies so that teaching and learning activities can take place in a systematic, directed, unobstructed, effective and efficient manner and can achieve educational targets. Contextual learning is a learning strategy that emphasizes the process of student involvement to achieve goals associated with real-life situations. The method used in this research is descriptive qualitative and data collection is done by interview and documentation as well as relevant literature. The results of the study on some high achieving students' motivation and interest in learning increased with the online learning method after the Christian Religious Education teacher carried out the role optimally by using contextual learning strategies.Â Â